A review of catalytic microwave pyrolysis of lignocellulosic biomass for value-added fuel and chemicals. (April 2017) - Morgan, Hervan Marion; Bu, Quan; Liang, Jianghui; Liu, Yujing; Mao, Hanping; Shi, Aiping; Lei, Hanwu; Ruan, Roger
Highlights: Review of catalytic upgrading of microwave-assisted pyrolysis (MAP) of biomass to desired products. Review of catalytic MAP of biomass for phenol rich and hydrocarbon rich bio-oil. Review of MAP and its increased efficiency in thermo-chemical conversion of biomass. Kinetics study and prospects for MAP of biomass are discussed. Abstract: Lignocellulosic biomass is an abundant renewable resource and can be efficiently converted into bio-energy by a bio-refinery. From the various techniques available for biomass thermo-chemical conversion; microwave assisted pyrolysis (MAP) seems to be the very promising. The principles of microwave technology were reviewed and the parameters for the efficient production of bio-oil using microwave technology were summarized. Microwave technology by itself cannot efficiently produce high quality bio-oil products, catalysts are used to improve the reaction conditions and selectivity for valued products during MAP. The catalysts used to optimize MAP are revised in the development of this article. The origins for bio-oils that are phenol rich or hydrocarbon rich are reviewed and their experimental results were summarized. The kinetics of MAP is discussed briefly in the development of the article. Future prospects and scientific development of MAP are also considered in the development of this article.